Correlation Between Visiting Posyandu and Hypertension Prevention Among the Elderly at Simpang Tiga Public Health Center, Pekanbaru City - Ezalina, Ezalina; Herlinda, Santi; Alfianur, Alfianur (RRZ Scientific Publishing, 2024)
Hypertension is a common condition among the elderly that can lead to serious health complications if left untreated. The prevalence of hypertension in Pekanbaru City tends to increase with age, and it is more common among the elderly. Approximately 8.1% of people in Simpang Tiga Public Health Center (PHC) live with hypertension. The purpose of this study was to determine the relationship between elderly visits to posyandu and the prevention of hypertension in the elderly. This research method used a quantitative approach with a cross-sectional design. We conducted this research at the Simpang Tiga PHC in Pekanbaru City from January to July 2023, using a questionnaire to assess visits to the elderly and prevent hypertension. This study used purposive sampling technique. The sample for this research was 74 elderly. The analysis used was the frequency distribution and the chi-square test. There was a relationship between elderly visits to posyandu and the prevention of hypertension (p<0.001, OR=3.06, 95%CI=1.756-5.336). We recommend conducting a longitudinal or intervention study to provide deeper insights and assist in the development of more effective strategies for the prevention of hypertension in the elderly.